Combining behaviourist and interactionist approaches to explain applicants’ attraction to organizations - Neves, J.; Gomes, D.R. (International Journal of Human Resources Development and Management, 2019)
This study discusses a model of analysis integrating interactionist and behaviorist theoretical guidance to explain applicants' attraction to organizations. rnThrough confirmatory methodology, we sustain a theoretical model pointing organizational attractiveness and perceived p-o fit as sequential mediators of the path starting on the organizational attributes and explaining intention to apply to a job vacancy. We justify our theoretical model along with a discussion regarding the integration of interactionist and behaviourist theoretical guidance to explain applicants' intention to apply to a vacancy.rnMain results point that main results sustain our theoretical model. The organizational attributes lead to attractiveness of the organization. This positive affective reaction is critical for prospective applicants to perceive to be fitted to the organization. This sequence of relations explains applicants' intention to apply to a job vacancy.rn .